I want a pet - Child, Lauren (London : Frances Lincoln Children's Books, 2007)
A girl tries to select a pet that will not eat her, be a copycat, make too much noise, or leave dirty footprints around the house.
2.6
K-3.
K-3
Keywords: Pets -- Juvenile fiction; Pets -- Fiction; Pets -- Fiction; Picture books for children